European monetary integration after EU enlargement - Klaus-Jürgen Gern; Felix Hammermann; Rainer Schweickert; Lúcio Vinhas de Souza (Institut für Weltwirtschaft (IfW), 2004)
Expectations about additional short-run gains from joining monetary union should not be too optimistic. Most of the expected gains from a monetary union are largely endogenous to credible, time-consistent domestic policies. Mere euro area membership is not a replacement for that. However, monetary integration has a role in supporting such policies and completing monetary integration, i.e., introducing the common currency can lock in the gains realized so far. The new member states made considerable progress with respect to the monetary and fiscal Maastricht criteria but inflation is still a concern in some countries and fiscal deficits are considerably too high for the majority of countries. However, experience with the run-up to EMU in the second half of the nineties shows that disinflation and fiscal consolidation can be achieved without major damage to growth. Additionally, structural real appreciation is unlikely to lead to an inconsistency of the inflation and the exchange rate targets. The experience with the currency board systems in Estonia, Lithuania, and Bulgaria reveals no evidence that the absence of an active exchange rate policy exacerbated the effects of external shocks. However, at the same time, the discipline demanded by the currency board system may have supported structural reforms. Hence, for countries which are determined to introduce the euro a currency board system may help to establish and maintain credibility within a consistent macroeconomic strategy. The experience with inflation targeting in Poland, the Czech Republic, and, more recently, Hungary shows that inflation targeting in general works successfully: it is not too soft because the Maastricht criteria guide the inflation target and it is not too rigid because new member states still need to establish credibility. The three countries should enhance the credibility of the inflation targeting regimes by thorough banking supervision and thorough fiscal policy. There is no generally superior exchange rate regime that provides a golden way to bridge the transition period to full EMU membership. While there is no reason to view monetary integration with rose-tinted glasses, there is also no reason to believe that joining the ERM II is sufficient to provide a safe haven with respect to financial stability. Even countries with sound and consistent macroeconomic policies and fulfilling all criteria - be it Copenhagen or Maastricht - will still run the risk that markets turn against them.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Konvergenzkriterien; EU-Staaten